2014
DOI: 10.1534/genetics.113.158279
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Pollen-Expressed Cullin1 Protein in Gametophytic Self-Incompatibility in Solanum

Abstract: We previously isolated a pollen factor, ui6.1, which encodes a Cullin1 protein (CUL1) that functions in unilateral interspecific incompatibility (UI) in Solanum. Here we show that CUL1 is also required for pollen function in self-incompatibility (SI). We used RNA interference (RNAi) to reduce CUL1 expression in pollen of Solanum arcanum, a wild SI tomato relative. Hemizygous T 0 plants showed little or no transmission of the transfer DNA (T-DNA) through pollen when crossed onto nontransgenic SI plants, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…Second, our genetic data established that both ui1.1 and ui6.1 are required to overcome the pistil UI barrier in SC × SI hybrids, which is consistent with the biochemical model in which each gene encodes components of the SCF complex. Third, we showed that CUL1 is required for pollenside SI function only if pistils express active S-RNase (8). Finally, the pollen determinants of SI specificity in the Solanaceae and related families with the S-RNase-based gametophytic self-incompatibility system are SLF proteins (2,6).…”
Section: Ui11mentioning
confidence: 79%
See 4 more Smart Citations
“…Second, our genetic data established that both ui1.1 and ui6.1 are required to overcome the pistil UI barrier in SC × SI hybrids, which is consistent with the biochemical model in which each gene encodes components of the SCF complex. Third, we showed that CUL1 is required for pollenside SI function only if pistils express active S-RNase (8). Finally, the pollen determinants of SI specificity in the Solanaceae and related families with the S-RNase-based gametophytic self-incompatibility system are SLF proteins (2,6).…”
Section: Ui11mentioning
confidence: 79%
“…In a compatible pollination, the SLF/S-RNase interaction leads to protection of pollen tubes against cytotoxic S-RNase, whereas in incompatible pollinations, a failure to recognize self-S-RNase results in pollen tube arrest. In addition, modifier genes, such as those encoding HT-B, NaStEP, and 120-kDa proteins in the pistil, and CUL1 and SSK1 proteins in pollen, are required for SI function but do not confer S-specificity (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
See 3 more Smart Citations